The readability of the world - Blumenberg, Hans (Cornell University Press and Cornell University Library, 2022)
"Hans Blumenberg has, in the quarter-century since his death, become recognized as one of the most important philosophers of the postwar period. The Readability of the World represents Blumenberg's first full-length demonstration of the metaphorological method he had pioneered twenty years earlier in Paradigms for a Metaphorology. Whereas Blumenberg had confined himself in Paradigms to sketching this future research field, in Readability he applies his method to a single case study: the idea that the world presents itself to human beings as a book. The metaphor of the book of nature has been central to Western interpretations of reality. Beginning with ancient Greek cosmology and ending with the genetic code, Blumenberg traces the changes undergone by this metaphor in order to access the different expectations of reality that it articulates, reflects, and projects"-- Provided by publisher.
"Originally published under the title Die Lesbarkeit der Welt, by Hans Blumenberg. ©Suhrkamp Verlag Frankfurt am Main 1981"--Title page verso.
Keywords: Science -- Philosophy.; Philosophy of nature.; Philosophie de la nature.; LITERARY CRITICISM / European / German; Philosophy of nature; Science -- Philosophy; Philosophy: metaphysics & ontology.; Philosophy.